Academic Pressure in Schools on Psychological Stress in Students - Pratanti Hernada; Aisha Nadia; Yoga Prima Putra (CV. Ksatria Siliwangi, 2025)
This study aims to analyze the forms of academic stress experienced by students and their impact on their psychological well-being, while also analyzing the role of schools and teachers in managing this stress. This study uses a qualitative approach with a phenomenological approach, focusing on understanding the subjective experiences of students and teachers in the context of academic stress. Data were collected through in-depth interviews, observations, and documentation with one vocational high school student and one Islamic junior high school teacher, then analyzed using domain analysis techniques to obtain a comprehensive picture in line with the research focus. The results show that academic stress significantly impacts students' learning motivation, concentration, emotional stability, and learning effectiveness. This stress stems from high grade demands, excessive workloads, exam anxiety, parental pressure, and a dense curriculum. Furthermore, limited guidance and counseling services in schools exacerbate the risk of academic stress, so management still relies on informal teacher initiatives. Nevertheless, students demonstrate adaptive strategies such as time management, prioritization, and seeking support to cope with stress. The conclusion of this study confirms that academic success is inseparable from students' psychological well-being at any level. Therefore, schools need to develop a more flexible and adaptive curriculum, provide structured, professional and sustainable counseling services, and encourage process-oriented learning and character building.